Green book - Farrelly, Peter; Vallelonga, Nick; Currie, Brian, 1961-; Mortensen, Viggo, 1958-; Ali, Mahershala, 1974-; Cardellini, Linda, 1975-; Maniscalco, Sebastian; Marinov, Dimiter D., 1964-; Hatton, Mike, 1978-; Lewis, Von, 1987-; Stark, Don, 1954-; Porter, Sean; et al. (Universal Pictures Home Entertainment, 2019)
When Tony Lip, a bouncer from an Italian-American neighborhood in the Bronx, is hired to drive Dr. Don Shirley, a world-class Black pianist, on a concert tour from Manhattan to the Deep South, they must rely on a book to guide them to the few establishments that were then safe for African-Americans. Confronted with racism, danger, as well as unexpected humanity and humor, they are forced to set aside differences to survive and thrive on the journey of a lifetime.